Exploring the determinants of midwives’ perinatal bereavement support behaviour to mothers using the theory of planned behaviour in the Upper West Region of Ghana - Veronica Sonasal Dooh; Evelyn Asamoah Ampofo; Adiza Atoko Mumuni; Michael Darko Ashaley; Mary Ani-Amponsah; Louis Nebayeng Mornah (PLoS ONE, 2026)
Background Perinatal loss presents profound emotional challenges requiring skilled bereavement support from midwives. Despite its importance, determinants of midwives’ bereavement support behaviour remain underexplored in low-resource settings. Using the constructs in the Theory of Planned Behaviour, this study examined factors influencing midwives’ bereavement support practices in Ghana’s Upper West Region. This study examined determinants of midwives’ behaviour in providing bereavement support to mothers experiencing perinatal loss in the Upper West Region. Methods A cross-sectional study was conducted among 269 registered midwives (response rate = 98%) across selected health facilities. Data were collected using structured questionnaires based on the Theory of Planned Behaviour (TPB). Analyses were performed in SPSS version 27.0 and AMOS, employing descriptive statistics, correlation analysis, and path analysis with bootstrapping to examine predictors of bereavement support behaviour. Results Among 269 midwives (response rate = 98%; mean age = 34 years), attitudes (M = 3.26, SD = 0.41) and perceived behavioural control (M = 3.02, SD = 0.57) were generally favourable. Path analysis revealed that attitude (β = 1.00, p < .001) and perceived behavioural control (β = .32, p < .001) significantly predicted behavioural intention, which strongly predicted actual behaviour (β = .65, p < .001). Notably, subjective norms had a negative effect (β = −.21, p < .001), and bereavement training were not statistically significant predictors of midwives’ bereavement support behaviour. Conclusion Midwives demonstrated favourable attitudes toward bereavement support, yet actual practice was primarily driven by personal attitudes and perceived control rather than training or social norms. To improve bereavement care, health systems should build midwives’ confidence through experiential training and mentorship, establish institutional cultures that normalize bereavement support, and integrate bereavement care protocols into routine maternal health services. These evidence-based strategies can enhance compassionate support for mothers experiencing perinatal loss in resource-limited settings.